The Effect of Discipline, Motivation, and Competence on Employee Performance Productivity in the Office Environment of the Class III Japura Airport Operator Unit - Komala, Yoga; Ali, Hapzi (Dinasti Publisher, 2025)
This study aims to determine whether discipline, motivation, and competence have a linear effect on employee performance and productivity at the Class III Japura Rengat Airport Operator Unit Office. This research model connects independent variables with dependent variables. Research objects are obtained from online sources such as Google Scholar and other online educational media. The method used is the research method using systematic literature review and library research with the use of Artificial Intelligence (AI)) to produce research according to the theme taken from e-books and open access journals. The output of this article is: 1) Discipline affects employee performance productivity; 2) Motivation affects employee performance productivity; and 3) Competence affects performance productivity.